Enhancement of Phenylpropanoid Accumulation and Antioxidant Activities of Agastache rugosa Transgenic Hairy Root Cultures by Overexpressing the Maize Lc Transcription Factor - Bao Van Nguyen; Jae Kwang Kim; Jinsu Lim; Kihyun Kim; Ramaraj Sathasivam; Dong Ha Cho; Sang Un Park (Applied Sciences, 2024)
Agastache rugosa is also known as Korean mint, and it has numerous health benefits due to its rich source of phenolic compounds. The main objective of this study was to produce a ZmLC-overexpressing transgenic hairy root line via Agrobacterium rhizogenes-mediated transformation. The overexpressing transgenic lines were screened using qRT-PCR after exposure to light conditions. The best hairy root line was selected, and the expression levels of phenylpropanoid biosynthetic pathway genes and phenylpropanoid compound accumulation were analysed using qRT-PCR and HPLC, respectively. In addition, antioxidant activities (RPA, ABTS, and DPPH), total phenolic content, and total flavonoid content were analysed. The ZmLC-overexpressing transgenic line upregulated all the phenylpropanoid pathway genes, which led to the higher accumulation of phenylpropanoid compounds in the transgenic line than in the control line. In addition, the total phenolic and flavonoid content was significantly higher in the transgenic line. The antioxidant activity assay showed that the transgenic hairy root line had significantly higher activity than that of the control lines. Thus, ZmLC positively enhances the phenylpropanoid biosynthetic pathway and antioxidant activities in A. rugosa. The results show that ZmLC can be used to enhance phenylpropanoid compounds and antioxidant activities in transgenic A. rugosa hairy root lines via the genetic engineering approach.